2011
DOI: 10.1093/ndt/gfr317
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of bone mineral density and biochemical markers of bone turnover in predicting fracture in CKD stage 5D patients--a single-center cohort study

Abstract: Hemodialyzed patients with low or high PTH or increased b-AP had a high fracture risk. BMD by Dual Energy X-ray Absorptiometry (DEXA), especially at the total hip region, was useful to predict any type of incident of fracture for females with low PTH or to discriminate prevalent spine fracture for every patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
211
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(223 citation statements)
references
References 21 publications
7
211
1
4
Order By: Relevance
“…(4) There were 46 fractures over 40 months, and low BMD at the hip and 1/3 radius predicted fractures. There are no studies in CKD patients not yet on renal replacement therapy (RRT).…”
Section: Introductionmentioning
confidence: 94%
“…(4) There were 46 fractures over 40 months, and low BMD at the hip and 1/3 radius predicted fractures. There are no studies in CKD patients not yet on renal replacement therapy (RRT).…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, it has been shown in a population of 2754 elderly subjects, including 587 subjects with CKD, that lower BMD was a risk factor associated with skeletal fractures 89. Several other recent papers have shown that low BMD actually predicts fracture in dialysis and renal transplant patients 90, 91. The use of micro‐computerized tomography might also be a useful tool for the estimation of bone loss and micro‐architectural changes; however, they need further evaluation in CKD 92.…”
Section: Bone and Musculoskeletal Abnormalities In Chronic Kidney Dismentioning
confidence: 99%
“…Furthermore, unlike PTH, concentration of bALP directly reflects osteoblastic activity, does not accumulate in blood with declining renal function (66), and is strongly and independently related to bone mineral density (67,68). It is also a good predictor, with dual-energy x-ray absorptiometry-derived bone mineral density values, of future fracture risk in patients undergoing dialysis (69). Biologic variation of bALP is approximately half that of PTH (70).…”
Section: Pth or Alp: Combine For The Best Of Both Worldsmentioning
confidence: 99%